Recommendations and measures for minimally invasivesurgery and endoscopic interventions during the COVID-19 pandemic - Lıman, Rumeysa Kevser; Dincer, Mürşit (My University, 2020)
The new severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2), which broke out in Wuhan province of China in December 2019, was declared as a pandemic in March 2020. Within the scope of combatting the pandemic, all non-urgent non-cancer-related elective procedures were halted worldwide. Due to concerns that the virus transmission is primarily via droplets and contact, as well as airborne transmission during aerosol-generating procedures, minimally invasive surgery and endoscopy have led to concerns that there may be procedures that carry the risk of virus transmission. The aim of this article is to report clinical recommendations and scientific studies in order to assist surgeons and endoscopists dealing with minimally invasive surgery
Keywords: Genel ve Dahili Tıp; Cerrahi